Implementation of the CTL Model with the CEP Approach to Improve Student Learning Outcomes and Entrepreneurial Interest in Matter–Properties and Changes in Vocational School - Zia Ulhaq, Muhammad; Wijayati, Nanik; Sumarni, Woro (Universitas Negeri Semarang, 2021)
The results of studying and entrepreneurial interest of students of SMK (Vocational School) Nusantara in Cirebon are still low. The learning strategies were used by teachers are generally conventional and not optimal for improving the learning outcomes and entrepreneurial interest of the student in schools. The type of research method used in this research is an experiment. The research data analysis technique used is the independent sample t-test. The result of this study is (1) the value of Sig. (2-tailed) obtained at 0.004 < 0.05 means there is an influence on the use of the CTL learning model with the CEP approach to improving student learning outcomes. (2) The test value of the Independent sample t-test sig. (2-tailed) amounting to 0.000 < 0.05 which means that there is an average difference in student learning outcomes between the experimental groups and the control, in other words, the application of the CTL model with the CEP approach with other learning methods will result in indifferent learning. (3) the test result of N-gain experimental class 58.03% (quite effective) while control group 34.38% (less effective) the results of this research are expected to be one of the solutions for educational practitioners, especially in vocational schools to equip students with entrepreneurial skills to reduce the impact of unemployment.